LARYNGOTRACHEAL TRAUMA MANAGEMENT AND ASSOCIATED MORBIDITY AND MORTALITY: 4-YEAR EXPERIENCE AT A TERTIARY CARE CENTER - PARMAR, SONU; AHUJA, PARIDHI; GUPTA, RASHMI; GOYAL, DIVYA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Cut throat injuries pose a great therapeutic challenge due to the multiple vital structures that are vulnerable to injuries in a small, confined unprotected area. In this study, we describe the site and depth of the injury, etiology, management, and prognosis. Methods: This was a retrospective study of 18 laryngotracheal trauma patients treated at the department of ENT in MDM hospital between April 2017 and January 2020. Results: Out of 176 cases of penetrating neck injury, 18 patients presented with a breach in the laryngotracheal framework. Male: female ratio was 17:1. The peak age of incidence is in the 2nd and 4th decade of life. Accidental cut throat injury was the most common mode of injury (83%), followed by homicidal (11%) and then suicidal (5%). Endotracheal intubation (where possible) or emergency tracheostomy was done to secure the airway in all the cases, followed by surgical debridement and laryngeal/hypopharynx repair. Post-operative endoscopy is useful to identify complications. Wound dehiscence was the most common complication. Conclusion: Cut throat injuries are one of the common ENT surgical emergency. Timely intervention is paramount, because it may otherwise cause death of the patient. Securing the airway, control of hemorrhage, and fluid and blood replacement is the mainstay to prevent complications such as shock, sepsis, laryngeal stenosis, or fistula formation.